Antibiotic Resistance and Biofilm-Forming Ability in Enterococcal Isolates from Red Meat and Poultry Preparations - Castaño-Arriba, Ana (Pathogens, 2020)
This study investigated the resistance to antibiotics and the capacity to form a biofilm of 200 isolates of enterococci isolated from raw preparations of beef (51 strains), pork (47), chicken (50), and turkey (52) acquired in north-western Spain. Fifteen antimicrobials of clinical importance were tested by the disc diffusion method. The average number of resistances per strain was 4.48 ± 1.59. If resistant strains were taken together with those showing reduced susceptibility, the total number of resistances per strain was 6.97 ± 2.02. Two isolates (1.0% of strains) were resistant to a single antibiotic, twenty-two isolates (11.0%) presented resistance to two, one strain (0.5%) was resistant to three, and 175 isolates (87.5%) showed a multiple drug-resistant phenotype (MDR; defined as no susceptibility to at least one agent from each of three or more antimicrobial categories). The prevalence of resistance varied between 0.5% (gentamicin) and 100% (kanamycin). All strains produced biofilm on polystyrene microwell plates, determined using crystal violet assay. Isolates were classified as having a weak (51 strains; average optical density at 580 nanometers -OD(580)- = 0.206 ± 0.033), moderate (78 strains; average OD(580) = 0.374 ± 0.068), or strong (71 strains; average OD(580) = 1.167 ± 0.621) ability to produce biofilm (p < 0.05). Isolates from beef preparations produced the most substantial (p < 0.05) biofilms. The results of this study indicate that meat and poultry preparations are major reservoirs of antibiotic-resistant enterococcal strains capable of forming a biofilm. In order for food-borne infections to be prevented, the importance of careful handling of these foodstuffs during preparation, avoiding cross-contamination, and ensuring thorough cooking, is stressed.